Cerebral vein thrombosis as the initial presentation of acute promyelocytic leukemia (APML) - Fizza Zulfiqar; Noora Khadoori; Lisa Deptula; Geetha Krishnamoorthy (Journal of Rare Diseases)
Abstract A 33-year-old woman with morbid obesity, positive IgM cardiolipin antibody, and recurrent venous thromboembolism on weight-based enoxaparin treatment developed severe headaches during her 9th week of pregnancy and was diagnosed with cerebral vein thrombosis (CVT). She was treated with enoxaparin (1 mg/kg) 240 mg twice daily, after a few days of intravenous heparin. Her complete blood count showed mild pancytopenia, with normal peripheral smear. She had a normal bone marrow biopsy done due to leukocytosis a year ago. She few days later presented to our emergency department (ED) with worsening headache and photophobia. Workup revealed normal anti-Xa activity despite weight-based enoxaparin, CVT, and a new diagnosis of acute promyelocytic leukemia. While it is known that APML predisposes to thrombotic events, there is limited literature that reports enoxaparin-resistant CVT as an initial manifestation of APML. It is important for clinicians to be aware that occurrence of unusual thromboembolism may herald APML.